Galactagogue effects of banana flower extract on lactating rats - Omar, Muhammad Nor; Mahmood, Azizah; Ngah, Nurziana (2010)
Study on the effect of banana flower extract on lactating rats was carried out. It was found that the amount of milk consumed by the pups increased in days of lactation, except when the dam did not feed their pups during a period of one hour milking. Besides that, the statistical data showed that there was a significant difference (p<0.5) in milk yield in lactating rats between the control group and petroleum ether extract group.